Análise de vibração em máquinas agrícolas em operações de campo - Silva, Maria Teresa de Rezende e (2021)
It is unquestionable the contribution of the agricultural mechanization to the growth of the agricultural sector throughout the 20th and 21th centuries. the large-scale food production reaches unprecedent productivities, due to the constant modernization of machines, implements, services, improvements in genetics, fertility, among other factors that contribute to the agribusiness. However, the machine operators are exposed to mechanical vibrations and they can suffer negative consequences along the years of work. The exposure to vibrations can cause health problems to the operator, problems that are signaled by low back pain and musculoskeletal disorders. Vibrations transmitted to machine operator through the operator's cabin seat are classified as whole body vibrations (VCI) as they are transmitted from the contact surface to the whole body. This study aimed to evaluate the vibration severity that affects the seat of the agricultural machinery in field conditions. Vibrations levels were analyzed through the RMS (Root Mean Square) acceleration and the frequency spectrum, in order to compare the results with the ISO 2631-1 (1997) standard, which concerns human exposure to mechanical vibrations. The transmissibility of vibration from the axles to the cabin floor and from the cabin floor to the operator's seat were also measured, with the objective of verifying whether the vibrational load that reaches the operator is amplified or reduced. A tractor, a mechanized set composed by tractor and a seeding-fertilizer machine, and a self-propelled sprayer were instrumented for the acquisition of acceleration data, regarding the longitudinal, transversal and vertical axes. An experiment was carried out with the tractor operating without coupling. In this experiment, the factors of operational speed, slope and inflation pressure of tires were considered and resulted in RMS accelerations, in the operator's seat, were analyzed according to the ISO 2631-1 (1997) standard, indicanting that the results of comfort of the operator were classified at uncomfortable and very uncomrotable categories. Experiments were also carried out to compare the operation of the coupled and uncoupled tractor to a seeder-fertilizer machine, in which the factors considered were the operational speed and the slope, in which the results of the RMS accelerations in the operator's seat were classified as “uncomfortable” and “very uncomfortable”, according to ISO 2631-1 (1997). Finally, a self-propelled sprayer was evaluated, in which the factors of operational speed and tires inflation pressure were considered. For the self-propelled sprayer, the RMS acceleration values at the operator's seat were framed as “uncomfortable” and “very uncomfortable”, according to ISO 2631-1 (1997). For the transmissibility from the rear axle to the cabin’s floor, in all experiments, the results indicated values were higher than 1, which may be related to the position of the rear axle in relation to the cabin floor, and also due the presence of double wheels in this axle. For the transmissibility of the cabin floor from the operator's seat, the values were less than 1, validating the seats damping, which reduce the vibrational levels to which the operator is exposed. Therefore, for eight hours of work a day, according to ISO 2631-1 (1997), for the operator's seat in all experiments, the vibrational load received by the operator was above that regulated by the standard, even though the structure of the seat reduces the vibration transmitted to the operator.